1999
DOI: 10.1038/sj.bjc.6694223
|View full text |Cite
|
Sign up to set email alerts
|

131I-metaiodobenzylguanidine (131I-MIBG) therapy for residual neuroblastoma: a mono-institutional experience with 43 patients

Abstract: Incomplete response to therapy may compromise the outcome of children with advanced neuroblastoma. In an attempt to improve tumour response we incorporated 131 I-metaiodobenzylguanidine ( 131 I-MIBG) in the treatment regimens of selected stage 3 and stage 4 patients. Between 1986 and 1997, 43 neuroblastoma patients older than 1 year at diagnosis, 13 with stage 3 (group A) and 30 with stage 4 disease (group B) who had completed the first-line protocol without achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 23 publications
1
48
1
2
Order By: Relevance
“…Our results are different from Garaventa et al, 1999 concerning stage III neuroblastoma, this may be attributed to the fact that stage III disease patients are already advanced from the start, also may be because we used the same doses of MIBG for both groups [20].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are different from Garaventa et al, 1999 concerning stage III neuroblastoma, this may be attributed to the fact that stage III disease patients are already advanced from the start, also may be because we used the same doses of MIBG for both groups [20].…”
Section: Discussioncontrasting
confidence: 99%
“…They reported that MIBG therapy showed very good partial response in 4/13 patients with stage III neuroblastoma, 1 patient showed disease progression and 8 patients showed stable disease. Regarding stage IV patients, 1/30 patients showed CR, 10 patients showed PR, 15 patients had no response to MIBG therapy and 4 patients showed progressive disease [20]. They stated the 5-year event-free survival (EFS) of stage III neuroblastoma to be 92% (±0.07) and that of stage IV to be 40% (±0.08) [20].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However the presence of radioactive compounds in the lungs may worsen a pre-existing immunodeficiency leading to a growth of opportunistic agents. 11 The increased risk of pneumopathy reported in lymphoma patients treated with 131 I-charged monoclonal antibodies could support this hypothesis. 12 Moreover, radioactive compounds are observed in the lungs very early on.…”
Section: Bone Marrow Transplantationmentioning
confidence: 94%
“…Последние десятилетия во многих протоколах лечения нейробластомы, например в NB2004, используется системная радиотерапия 131 I-MIBG, которая показала свою эффективность как у пер-вичных больных, так и у пациентов с рецидивами [19][20][21].…”
Section: Discussionunclassified